Targeted Delivery of Pesticides Using Biodegradable Polymeric Nanoparticles - De, Arnab; Bose, Rituparna; Kumar, Ajeet; Mozumdar, Subho; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2014)
The brief is the first to focus exclusively on environmentally friendly delivery of pesticides (controlled-release nanoparticulate formulation of pesticides using biodegradable polymers as carriers). The brief also introduces pesticides like Chlorpyrifos and biodegradable polymers like guar-gum. The brief will be extremely useful to the researchers in the field of agrochemicals and will be equally useful for advanced professionals in the field of biology, chemistry, environmental biology, entomology and horticulture.
Introduction -- World-wide Pesticide Use -- Pesticide Application in India -- Food Contamination and Wastage by Insects -- Pesticide Formulations -- Trends and Limitations in Chemical-based Pest Management -- Biological Control of Insect Pests -- Management of Insect-pests Using Nanotechnology as Modern Approaches -- A Brief Overview of Nanotechnology -- Nanoparticulate Delivery Systems -- Nanoparticulate Formulations for Pesticide Applications -- Characterization and in vitro Release Techniques for Nanoparticulate Systems -- Reference.
Keywords: Chemistry; Bioorganic chemistry; Nanochemistry; Environmental chemistry; Chemistry; Bioorganic Chemistry; Nanochemistry; Environmental Chemistry